Site-Specific Fertilizer Management through Nutrient Expert: Productivity, Profitability and Efficiency of Wheat (Journal of Tikapur Multiple Campus, 2023)
A field experiment was conducted at Tikapur, Kailali located in Sudur-Pashim Province of Nepal from November 2021 to April 2022 to determine the effects of site-specific nutrient management practice son the yield, economics and resource use efficiency of wheat (cv: Vijay). Six fertilizer treatments were laid-out in a Randomized Complete Block Design. The treatment includes nitrogen omitted plot (N0), blanket recommendation (BR), Nutrient Expert based-NPK (NE), Nutrient Expert based nitrogen recommendation and farmers fertilizer practice for other fertilizers (NE-N), leaf color chart-based nitrogen recommendation (LCC-N) and farmers fertilizer practice (FFP). NE produced the highest yield compared to BR and FFP. Grain yield between NE and LCC was similar (p>0.05). LCC-N produced the highest harvest index (0.46) and nitrogen use efficiency while they were the lowest in farmer-based practice. As with yield, NE produced higher gross revenue and benefit-cost ratio compared to farmers’ practice. Similarly, the maximum nitrogen uptake by grain and straw and soil residual N was observed in NE treated plot. These results suggested that NE based NPK management could increase yields, NUE and farm profit. However, similar benefits could also be achieved using either LCC based N management with 25 to 40% less N compared to NE. So, the fertilizer recommendation using NE-Wheat model in combination with LCC (if available to farmers) for N management could be suggested to the farmers for successful wheat cultivation.